2018
DOI: 10.5539/cis.v11n1p52
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Classification Model Using Sentiment Analysis on Twitter Based on Hybrid Naive Bayes Classifiers

Abstract: Sentiment analysis has become one of the most popular process to predict stock market behaviour based on consumer reactions. Concurrently, the availability of data from Twitter has also attracted researchers towards this research area. Most of the models related to sentiment analysis are still suffering from inaccuracies. The low accuracy in classification has a direct effect on the reliability of stock market indicators. The study primarily focuses on the analysis of the Twitter dataset. Moreover, an improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…First, it represents the datasets as a corpus then constructs a document term frequency matrix (DFM) to represent the records as word counts; this is called a 'bag-of-words' approach. The model creates the frequency table for each word in the training data against each class and determines the initial weight for every record [43]. The model calculates the probability of each word in the class and the probability of the class.…”
Section: Classification Modulementioning
confidence: 99%
“…First, it represents the datasets as a corpus then constructs a document term frequency matrix (DFM) to represent the records as word counts; this is called a 'bag-of-words' approach. The model creates the frequency table for each word in the training data against each class and determines the initial weight for every record [43]. The model calculates the probability of each word in the class and the probability of the class.…”
Section: Classification Modulementioning
confidence: 99%
“…High classification accuracy with real sentiment analysis will produce reports and indicators that are accurate and reliable on company shares. from these results, it can be seen that machine learning methods that use sentiment analysis on Twitter such as the NB classifier produce high, real and reliable accuracy by simulating domain features and preparing datasets using the NLP method [3].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Nisar and Yeung [166] collected a sample of 60,000 tweets made over a six-day period before, during, and after the local elections in the United Kingdom to investigate the relationship between their content and the changes in the London FTSE100 index [166]. Similarly, many other researchers use the information available on Twitter to make stock market predictions [167][168][169][170][171][172][173][174][175]. Öztürk and Ayvaz [163] studied Turkish and English tweets for evaluating their sentiments towards the Syrian refugee crisis and found that Turkish tweets are remarkably different from English tweets [163].…”
Section: Twittermentioning
confidence: 99%